Understanding the genetic nature of some mental disorders. 1q21.1 chromosome deletion syndrome. Short review - Orlova, Nataliia (Psychosomatic Medicine and General Practice, 2019)
By studying genes, genetic variation and heredity, genetics opens the veil and enriches us with new knowledge about the nature of neuropsychiatric diseases. Appears, that both widespread and well-known diseases and very rare disorders not quite understood to science mostly are genetically determined and occupy certain areas (loci) in certain chromosomes, like books on the shelves in the library. Many chromosomal abnormalities manifesting behavioural and mental disorders are already known today. The article highlights new knowledge about behaviour disorders associated with the first largest human chromosome. Various failures, such as deletion, microdeletion, or duplication at certain loci of this chromosome, it seems to play a significant role in the appearance of both well-known and poorly understanding neuropsychiatric disorders. Emphasis is placed on the deletion syndrome of its long shoulder - 1q21.1 chromosome deletion syndrome. The ideogram of the first chromosome is pointed below, and the abnormal loci are clearly identified and discussed. Modern diagnostic techniques used to determine chromosomal abnormalities are highlighted, and the possible mechanisms of the heritability is analyzed and discussed. Examples of possible clinical manifestations that have ever been found in carriers with this syndrome and methods of treatment and rehabilitation are underlined as well. An important point is that an attempt is made to summarize knowledge of disorders caused by deletion and duplication of the long arm of chromosome 1q21.1. Scientists are actively seeking all possible links in the development of schizophrenia and autism in carriers. The importance of understanding and knowing this is an integral part of the diagnostic and therapeutic processes for a modern psychiatrist. It is important to take this into account during the first meeting and talking with relatives or the patient himself. In addition, it is of great importance for the management of patients with the syndrome and for understanding the consequences and prognosis of neuropsychiatric disorders.